Integrated remote sensing and GIS techniques to delineate groundwater potential area of Chamchamal basin, Sulaymaniyah, NE Iraq - Diary Ali Mohammed; Sarkhel H. Mohammed; Péter Szűcs (Kuwait Journal of Science)
Abstract